2013
DOI: 10.5539/jas.v5n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Inclusion of Conjugated Linoleic Acid on Quality Indicators of Aged Pork Loin

Abstract: The purpose of this study was to examine the effect of dietary inclusion of conjugated linoleic acid (CLA) in hog feed on quality indicators of pork loins. A total of twenty barrows (PIC 380 x Cambrough 1025) were randomly paired, housed in pens, and fed 1% soybean oil or 1% CLA diet for 6 weeks. There were no significant differences in proximate composition of the pork loins (P > 0.05). Muscle pH increased and there were color changes over time (P < 0.05) which was independent of diet (P < 0.05). Shear force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Regarding the meat quality parameters, no effects due to the use of CLA were found on pH, colour, WBSF, or cooking loss when compared to RAC. These results are consistent with those reported by Matak et al (2013), who evaluated CLA 1% for 6 weeks in 20 barrows and did not find an effect on these meat quality characteristics. In the pork steak shelf life study, initial TBARs values were low (0.208-0.324); however, at the end of the storage period, only meat from animals treated with CLA 1% had values below 1.4 mg of MDA, which has been considered the lower limit to detect unpleasant odours characteristic of meat lipid rancidity by consumers (Wenjiao et al 2014).…”
Section: Meat Qualitysupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the meat quality parameters, no effects due to the use of CLA were found on pH, colour, WBSF, or cooking loss when compared to RAC. These results are consistent with those reported by Matak et al (2013), who evaluated CLA 1% for 6 weeks in 20 barrows and did not find an effect on these meat quality characteristics. In the pork steak shelf life study, initial TBARs values were low (0.208-0.324); however, at the end of the storage period, only meat from animals treated with CLA 1% had values below 1.4 mg of MDA, which has been considered the lower limit to detect unpleasant odours characteristic of meat lipid rancidity by consumers (Wenjiao et al 2014).…”
Section: Meat Qualitysupporting
confidence: 93%
“…Partial sums of fatty acids and nutritional value of the intramuscular fat of the longissimus thoracis muscle per treatment. study, Matak et al (2013) found no effect on the addition of 1% of CLA in the finishing diets of pigs on lipid oxidation of meat. Similarly, in the present study, meat obtained from animals supplemented with CLA had a higher percentage of some SFAs, which promoted a decrease in the susceptibility to oxidation.…”
Section: Meat Qualitymentioning
confidence: 87%